Exploring self-regulated writing strategies: A comparison between paragraphs and essays - Ratih Novita Sari; Atik Umamah; Merliyani Putri Anggraini; M. Affandi Arianto; Kurniasih Kurniasih; Nur Mukminatien (Universitas Syiah Kuala, 2023)
Writing requires a complex skill, and thus students need to regulate themselves in employing the appropriate strategies to achieve good writing performance. The present research investigated Self-Regulated Writing (SRW) strategies used by EFL (English as a Foreign Language) university students. It contrasted the students' strategies related to the complex structure of the texts (i.e., paragraphs and essays) and students’ writing performance. The data information came from two separate sets of self-regulated learning strategy questionnaire, as well as writing outcomes of the students. Descriptive statistics and the Mann-Whitney U test were utilized to evaluate the data. The six dimensions of SRW strategies were extensively utilized in paragraph and essay writings. The six dimensions include motive, method, time, performance, physical environment, and social environment. Interestingly, the social environment dimension had the highest mean score, showing that the students needed assistance from their peers and available learning resources. Meanwhile, the motive dimension obtained the lowest mean in both paragraph and essay writings. Furthermore, the analysis showed no significant statistical difference in using SRW strategies in writing paragraphs and essays except in the method dimension. The difference in strategy use based on achievement was also not significant. The results indicate that the students applied similar SRW strategies in paragraph and essay writings regardless of their proficiency levels. Pedagogical implications and recommendations for future research are also further discussed in the article.